ANALISIS PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING PADA PT PLN (PERSERO) UIP SULBAGUT - Galla, Cosmas Mariones; Tewal, Bernhard; Jan, Arrazi Hasan (FEB Universitas Sam Ratulangi Manado, 2020)
Nowadays HR has become one of the most important assets in an organization so it must receive the best appreciation. Employee performance appraisal data at PT PLN (Persero) UIP SULBAGUT during the last 3 semesters has decreased, although in semester 2nd of 2019 there were additional employees who were likely to influence the performance appraisal so that it became better. Researcher see that this phenomenon occurs because of a decrease in work motivation, career development uncertainty and also employee job dissatisfaction. Based on the survey, the majority of PLN UIP SULBAGUT employees are already working with high motivation. But for the promotion system, rotation and employee performance appraisal, apparently not all employees can accept the system that runs so far. The purpose of this study was to analyze the effect of work motivation and career development on employee performance with job satisfaction as an intervening variable at PT PLN (Persero) UIP SULBAGUT. This research is a quantitative study by distributing questionnaires to 107 respondents from a population of 146 employees at PT PLN (Persero) UIP SULBAGUT along with the Sub-Units below. Data analysis in this study was using path analysis. The results of this study indicate that work motivation and career development simultaneously and partially have a positive and significant effect on job satisfaction. Work motivation, career development and job satisfaction simultaneously and partially have a positive and significant effect on employee performance. Work motivation and career development partially have a positive and significant effect on employee performance both directly and indirectly through job satisfaction.Work Motivation, Career Development, Job Satisfaction, Employee Performance.